Evaluation of Risk Factors of Surgical Site Infections After a Lower Segment Cesarean Section in Bahrain - A Retrospective Analytical Study - Hasan Almajed; Yusuf Jalili (Journal of the Bahrain Medical Society)
Background: Surgical Site Infections (SSI) impose a critical complication following lower segment cesarean sections (LSCS), contributing significantly to maternal morbidity and mortality. Understanding the risk factors associated with SSI is essential for improving clinical outcomes and enhancing patient care. This study aimed to identify the rate and risk factors associated with SSI among women who underwent LSCS at Salmaniya Medical Complex (SMC) in Bahrain. Methods: A retrospective observational study was conducted at SMC in the period between 2020 and 2023. All patients with SSI post-LSCS and a comparable sample of patients who underwent LSCS but had no SSI were included. Data including patient demographics, clinical characteristics, and specific risk factors related to SSI were collected from electronic medical records. Descriptive and inferential analyses were done. Results: The rate of SSI was 2.1% among women who underwent LSCS in SMC. Predictors of higher rates of SSI post-LSCS included having an emergency LSCS (odds ratio [OR]=4.14), a longer hospital stay (OR 1.37), and pre-operative stage 1 hypertension (OR=2.66), while diabetes mellitus (OR=0.29) and post-operative elevated laying blood pressure were linked to a reduced risk (OR=0.42) of postLSCS SSI. Conclusion: This study revealed a low rate of post-LSCS SSI. This study highlighted the implications of emergency procedures, hospital stay duration, and blood pressure management. The paradoxical protective effect of diabetes mellitus warrants further investigation. These insights are pivotal for developing targeted interventions aimed at minimizing SSI, thereby enhancing maternal health outcomes in clinical practice. Keywords: Pregnancy, Female, Surgical Wound Infection, Cesarean Section, Risk Factors